A MATHEMATICAL MODEL FOR DIABETES MANAGEMENT - Kwaghkor, Lubem M.; Mohammed, A.; Nyamtswam, E. V. (FUDMA JOURNAL OF SCIENCES, 2022)
Treating and controlling of diabetes is called diabetes management. The management of diabetes can be done through improvement of the patient dietary knowledge, attitudes, and practices. This research work is aimed at introducing dietary (diet restriction) to an earlier model for the detection and control of diabetes: to study the effect of physical exercise and dietary on excess glucose, insulin and epinephrine concentrations in the blood in managing diabetes. The resulting model is found to be uniformly and asymptotically stable. The result shows that when physical exercise is combined with recommended dietary in the management of diabetes, the excess glucose, insulin and epinephrine concentrations returns to their normal level faster with time compared to when only physical exercise is used as a control measure. Hence, it is recommended that in the management of diabetes, both physical exercise and dietary should be used as control measures
Keywords: Diabetes, Dietary, Epinephrine, Glucose, Insulin, Physical Exercise